Kinerja Simpang Tak Bersinyal Pada Persimpangan Jl. Damang Batu Jl. Pilau Kota Palangka Raya - Rexy Lukas; Ina Elvina; Desi Riani (Jurnal Serambi Engineering, 2023)
An intersection refers to a designated area on the road network where traffic on vehicles sourced from several directions meets. The intersection of Damang Batu Road - Pilau Road is located in the urban area of Palangka Raya. This intersection is a very important traffic meeting point as it must facilitate rapid movement throughout the area. Analyzing the performance of the intersection is an important factor in identifying the most effective strategies to improve its efficiency. This study was conducted with the aim of analysing the intersection performance and obtaining alternatives to optimise the intersection performance. This research uses observational methodology, where data collection is carried out in a field situation. After all the data both primary and secondary are collected, the data will be analysed using the MKJI 1997. According to the results, under current conditions it has shown good results. The capacity value is 2434 smp/hour. And the degree of saturation is 0.51. Meanwhile, the intersection delay is 10.779 sec/smp. And the upper limit for queuing opportunities is 25%, the lower limit is 11%. So that the service level at that intersection falls into category B, indicating a good level of service.